UJI FITOKIMIA DAN UJI AKTIVITAS ANTIOKSIDAN (METODE DPPH) DARI DAUN RAMBAI (Baccaurea motleyana Mull. Arg.) - Ami, Suyatmi; Saleh, Chairul; Pratiwi, Djihan Ryn (JURNAL ATOMIK, 2019)
The research about phytochemical test and antioxidant activity test on rambai leaves extract (Baccaurea motleyana Müll.Arg.) using DPPH radical immersion method had been done. This research aims to know kinds of secondary metabolite compounds in rambai leaves extract and level of antioxidant activity in rambai leaf. The result of this research showed that the secondary metabolite in rambai leaf were alkaloids, phenolics, flavonoids, saponins, steroids and triterpenoids. IC50 values obtained in each crude extract, n-hexane fraction, ethyl acetate fraction and residual ethanol fraction were 13.27 ppm, 22.81 ppm, 19.22 ppm and 13.33 ppm respectively. The highest level of antioxidant activity was in crude extracts.